Motherhood for self-care: Challenges for building gender equity - Bitencourt, Silvana Maria (FCL-UNESP Laboratório Editorial, 2020)
The growing insertion of women in higher education and in the labor market in the recent decades contributes to reinforce some dilemmas in the construction of gender equity, which reflects the use of time for women to study, work, care for the family and take care of themselves. From this perspective, this work aims to identify how university women deal with motherhood and career building during the graduation phase. For this purpose, field work was carried out in two undergraduate courses and 10 semi-structured interviews were conducted in depth with students. We concluded that the vast majority of mothers present difficulties in reconciling motherhood and studies, some of them think of giving up their studies because they do not have a support network, just as there are no public policies which recognize the participation of the mother women in Brazilian universities.